Infrared Surveys to Search for High Proper Motion Stars - Malik, E. D.; Malkov, O. Yu.
There are restrictions on the nature and characteristics of nearby brown dwarfs (including hypothetical component of the Sun), imposed by the current results of the work of the Gaia space observatory. In particular, even close brown dwarfs of spectral type Y3 and colder will go unnoticed by the Gaia observatory, although they may well be already included in infrared survey catalogues. Here we present information on modern infrared surveys, which can be used for a search for such objects.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture